Persepsi Pembaca di Kota Denpasar Mengenai Pemberitaan Covid-19 oleh Tribun Bali - Manullang, Santa Monika; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
This study analyzes and describes how readers in Denpasar City decode discourse on Covid-19 news that has been encoded and published by the Tribun Bali. The method used is a qualitative approach with a descriptive explanative type. The theory used in this research is Stuart Hall’s encoding and decoding theory. Based on the theory, the writer groups the informants into three reader positions based on the perception given, namely the dominant hegemonic, negotiation, and oppositional positions. Through research conducted on five informants, the authors found that messages that had been encoded by Tribun Bali journalists were not always decoded symmetrically by the five informants. The author also finds that the five informants are not always in the same position as readers in every discourse on the encoded news and the position of the reader that is most often occupied is the dominant hegemonic position. Keywords: Covid-19, Tribun Bali, encoding dan decoding.